TIGAR regulated by HPV E6 is correlated with disease stage, drug sensitivity, and immune microenvironment in cervical cancer - Yameng Liu; Yu Zhang; Hailong Zhang; Dianqin Xu; Xinzhu Zhou; Luhong Xie; Hongli Xi; Yurong Zhu; Hanlin Yang; Xiaoyu Zhu; Ji Ren; Shaoju Min; et al. (Scientific Reports)
Abstract Cervical cancer is the fourth most common malignant tumor in women, lacking specific and sensitive markers. TP53 induced glycolysis regulatory phosphatase (TIGAR) plays an important role in the initiation and progression of several solid tumors. This study aims to investigate the diagnostic and prognostic and immunotherapeutic role of TIGAR in cervical cancer. We observed that TIGAR expression was upregulated in cervical cancer cells and tissues using experiments and bioinformatics analyses. Moreover, elevated TIGAR expression was associated with poor prognosis using Kaplan–Meier survival analysis, and its diagnostic value was confirmed using the Receiver operating characteristic (ROC) curve. We also analyzed the correlation between TIGAR expression and immune infiltration and assessed its correlation with a clinical cohort of cervical cancer, and found that TIGAR expression was significantly associated with the infiltration levels of Foxp3 + Treg cells, CD11b + MDSC, CTLA4, and HAVCR2. TIGAR is a potential diagnostic and prognostic biomarker of cervical cancer and is expected to offer new possibilities for cervical cancer immunotherapy.